The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1345/aph.1r094
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Problems and Hospital Admissions in Cardiac Transplant Recipients

Abstract: Hospital admissions following cardiac transplantation are often drug related (40%) and preventable (58%). Incorporating this insight into the multidisciplinary transplant team may improve outcomes, assist in meeting national quality mandates by the United Network for Organ Sharing and Centers for Medicare Services, and lead to new benchmarks for transplant centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 24 publications
5
36
0
Order By: Relevance
“…Another study reported that 40% (19 of 48) of read-missions in patients who had previously received a heart transplant were caused by DRPs and that 58% (11 of 19) of these were preventable. 16 These values are closer to those observed in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another study reported that 40% (19 of 48) of read-missions in patients who had previously received a heart transplant were caused by DRPs and that 58% (11 of 19) of these were preventable. 16 These values are closer to those observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…A study of 97 patients with heart failure found that one of the most frequent DRP detected (22%) involved inadequate dose, regimen, or duration of a drug, 7 while a study of 19 heart transplant recipients who were readmitted for a DRP found that the most common cause was an inappropriate dose (47.4%). 16 In our study, dose adjustment according to renal function was more frequent in patients with heart failure than in those with other cardiovascular diseases. In contrast, prescription errors caused by inadequate knowledge of the CPOE were less frequent in patients with heart failure than in those with other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This could be attributed to the fact that prospective studies allowed closer contact with the patients, which permitted more complete and accurate information to be obtained . In addition, the prospective studies used a wide variety of definitions for ADRs, which comprised not only WHO definitions , but also other definitions based on hazards, harm and poison prediction or classification of ADR types [29–30]. Similar to the retrospective studies, the severity and preventability were under‐reported.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the full text of the articles, only 19 were finally selected [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The main reasons for exclusion are summarized in Fig.…”
Section: Review Of Information and Definition Of Scenariosmentioning
confidence: 99%